Modification of postprandial lipid profiles in people with diabetes - Mohanlal, N; Mohanlal, Nina (2003)
﻿ Background: Abnormalities in postprandial lipid metabolism may explain, in part, the 2 to 4 fold increased risk of coronary heart disease (CHD) in diabetic individuals compared with the general population. Aims: To develop an Oral Triglyceride Tolerance Test (OTTT) to evaluate reliably post challenge metabolism and to determine whether more physiologic insulin profiles can improve lipid responses in diabetic subjects. Methods: Post 50g fat and 50g carbohydrate challenge triglyceride and glucose profiles were measured 2 hourly for 8 hours on 2 occasions to establish test reproducibility and to characterise responses in type 2 diabetic and non diabetic subjects. The potential effects on post challenge lipid and glucose metabolism of modifying endogenous insulin delivery via the portal system or augmenting post challenge systemic insulin levels were assessed using the OTTT. Results: Reproducible post challenge triglyceride, NEFA, glycerol, glucose, insulin and C peptide responses were obtained in non diabetic and type 2 diabetic subjects. In type 2 diabetic subjects both ultra rapid endogenous and exogenous insulin delivery decreased post challenge hyperglycaemia and improved NEFA-glycerol suppression, relative to placebo and soluble insulin respectively. Enhancing portal insulin secretion had no effect on triglyceride levels. Increasing peripheral insulin levels showed no difference in triglyceride profiles between insulins tested although 6 hour triglyceride excursions were less than endogenous enhancement. Type 1 diabetic subjects displayed triglyceride profiles similar to non diabetic subjects, and reduced triglyceride excursion was seen with soluble than analogue insulin replacement. Conclusion: Increasing the peripheral to portal insulin ratio may relieve hepatic exposure to chronic hyperinsulinaemia characteristic of type 2 diabetes thus reducing post challenge triglyceride excursions. Improving postprandial metabolism, by delaying atherogenesis, may help decrease the risk of CHD. 7